PENGARUH LILIT ULANG DAN PERUBAHAN JUMLAH KUTUB TERHADAP KINERJA MOTOR INDUKSI KOMERSIAL 1 HP YANG DIFUNGSIKAN SEBAGAI GENERATOR PADA PLTMh - , IBNU UDY PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The MHP always uses the prime mover which produces the low speed. One type of the generator which is always used on the MHP is the generator induction. Generator induction has the advantage, however it has the despite if it is compared to the synchronous generator. One of the disadvantage of the induction generator is on the efficiency, and the voltage regulation. The use of the low speed generators are expected to increase the efficiency of the mechanical transmission system. The purpose of this study is to determine the performance of the generator induction which was rewind and changed on the number of poles. The specification of the generator induction which was used is induction motor 3 phase 1hp 6 poles. The method which is used on this research is based on the experiment and comparison. The Induction motor and generator which have not been rewind became the reference. For the first time tested as a motor, and then tested as generator. After it was rewind by the 6 poles of numbers, then retested either as a motor or as a generator. Similarly, by the 12 poles of number. As a motor tested without load and locked rotor in the electric motor installation laboratory of SMKN 3 Kuningan, while as a generator tested at the MHP Singosaren, Wukirsari , Imogiri, Bantul Yogyakarta. The test of input by using prony brake but the test of the output by using incandescent lamp loads test. The result show that: as a motor induction, the result of the rewinding performance is expected. But as a generator induction has reduced performance, i.e. at efficiency of 62,03% becomes 50,40% on the voltage allowed by PLN (+ 10% x 220 volt). At the generator induction when it rewind, for the 12 poles of number has a decrease efficiency 31,01% on the 300 volt (> 10% x 220 volt).